Analysis of various degradations of five years aged mono c-Si, poly c-Si, and thin-film photovoltaic modules from rooftop solar installations in Dhaka’s tropical wet and dry climate conditions - Hossion, Abul; Manoj Kumar, Nallapaneni; Bajaj, Mohit; Alrashed, Mohammed M.; Elnaggar, Mohamed F.; Kamel, Salah (Frontiers in Energy Research, 2023)
This study evaluates the degradation of mono, poly, and thin-film silicon solar photovoltaic (PV) modules through visual and electrical measurements in Dhaka's tropical wet and dry climate conditions. For this, several sites of rooftop solar PV installations in Dhaka, aged at least five years, were selected for field investigation. A visible inspection of the PV modules on the rooftop for visible degradation due to environment and aging followed by real-time experimental testing on current-voltage (I-V) under the sunlight using a portable Seaward I-V Tracer for measuring the electrical degradation. The data sets were taken in August 2019, from 12:00H-14:00H under solar irradiation in the range of 800-1000 Wm-2. The electrical data were used to evaluate the degradation of short circuit current, open circuit voltage, fill factor, and maximum power after 5 years of operation in the field as compared to the nameplate values. The degradation of PV modules in terms of short circuit current was 0.7%/y for 85Wp mono c-Si, 7.6%/y for 150Wp poly c-Si, and 9.7%/y for 105Wp silicon thin-film, respectively. We believe this study would guide the maintenance of the solar PV systems installed on Dhaka city's rooftop buildings.